Somatosensory predictors of response to pregabalin in painful chemotherapy-induced peripheral neuropathy: a randomized, placebo-controlled, crossover study. Issue 8 (August 2019) - Hincker, Alexander; Frey, Karen; Rao, Lesley; Wagner-Johnston, Nina; Ben Abdallah, Arbi; Tan, Benjamin; Amin, Manik; Wildes, Tanya; Shah, Rajiv; Karlsson, Pall; Bakos, Kristopher; Kosicka, Katarzyna; et al.
Abstract : Abstract: Painful chemotherapy-induced peripheral neuropathy (CIPN) is a debilitating and treatment-resistant sequela of many chemotherapeutic medications. Ligands of α2δ subunits of voltage-gated Ca 2+ channels, such as pregabalin, have shown efficacy in reducing mechanical sensitivity in animal models of neuropathic pain. In addition, some data suggest that pregabalin may be more efficacious in relieving neuropathic pain in subjects with increased sensitivity to pinprick. We hypothesized that greater mechanical sensitivity, as quantified by decreased mechanical pain threshold at the feet, would be predictive of a greater reduction in average daily pain in response to pregabalin vs placebo. In a prospective, randomized, double-blinded study, 26 patients with painful CIPN from oxaliplatin, docetaxel, or paclitaxel received 28-day treatment with pregabalin (titrated to maximum dose 600 mg per day) and placebo in crossover design. Twenty-three participants were eligible for efficacy analysis. Mechanical pain threshold was not significantly correlated with reduction in average pain ( P = 0.97) or worst pain ( P = 0.60) in response to pregabalin. There was no significant difference between pregabalin and placebo in reducing average daily pain (22.5% vs 10.7%, P = 0.23) or worst pain (29.2% vs 16.0%, P = 0.13) from baseline. Post hoc analysis of patients with CIPN caused by oxaliplatin (n = 18) demonstrated a larger reduction in worst pain with pregabalin than with placebo (35.4% vs 14.6%, P = 0.04). In summary, baseline mechanical pain threshold tested on dorsal feet did not meaningfully predict the analgesic response to pregabalin in painful CIPN. Abstract : Supplemental Digital Content is Available in the Text.Baseline mechanical pain threshold does not predict analgesic response to pregabalin in painful chemotherapy-induced peripheral neuropathy caused by docetaxel, paclitaxel, or oxaliplatin.